2011
DOI: 10.1016/j.curtheres.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Postoperative Nausea and Vomiting After Laparoscopic Cholecystectomy: A Prospective, Randomized, Double-Blind Study

Abstract: Administration of a subhypnotic dose of 0.5 mg/kg propofol plus 8 mg dexamethasone at the end of surgery was more effective than administration of 0.5 mg/kg propofol plus metoclopramide in preventing PONV in the early postoperative period in adult patients undergoing LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 32 publications
0
27
0
2
Order By: Relevance
“…Nausea and vomiting due to surgery and anesthesia are among the most common complications. The reported incidence of PONV after LC varies from 50 to 70% [7][8][9][10]. There are many researches for prevention and cure PONV, such as using gabapentin, dexamethasone, perphenazine and so on, they all have efficacy and some side-effects more or less [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Nausea and vomiting due to surgery and anesthesia are among the most common complications. The reported incidence of PONV after LC varies from 50 to 70% [7][8][9][10]. There are many researches for prevention and cure PONV, such as using gabapentin, dexamethasone, perphenazine and so on, they all have efficacy and some side-effects more or less [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis by Si et al (25) revealed that the combination of dexamethasone plus other antiemetic agents is more effective than the single antiemetics for preventing PONV after laparoscopic cholecystectomy. Also, the study by Arslan et al (17) showed that combined propofol with dexamethasone is more effective in preventing PONV than combination of propofol plus metoclopramide. Although, metoclopramide is the most commonly used drug to prevent PONV, the previously published data have been in favour of dexamethasone in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of nausea/ vomiting was graded into 4 categories, scoring ranged from 0 (Without nausea) to 4 (Severe vomiting [continuous]). (17) In order to evaluate the severity of pain, Visual Analogue Scale (VAS) was used. VAS score ranges from 0 (no pain) to 10 (worst possible pain).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…At high doses metoclopramide associated with extrapyramidal effects such as akethesia motor restlessness etc. 2,8 Rationale of this study is to compare the efficacy of ondansetron and metoclopramide in patients undergoing laparoscopic cholecystectomy under general anesthesia. Many studies have compared the efficacy of ondansetron and metoclopramide, however on reviewing the literature, it was noticed that there is contradiction about the efficacy between both drugs.…”
Section: Introductionmentioning
confidence: 99%